2018
DOI: 10.18203/2319-2003.ijbcp20181187
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of tirapazamine as anti-cancer drug: a meta-analysis of randomized controlled trials

Abstract: Background: The benefits of achieving better response by adding tirapazamine, a specific hypoxic cancer cell killer to chemo and or radiotherapy is contradictory. This study aims at analyzing the efficacy and safety of tirapazamine, apart from understanding the reasons for its doubtful and inconsistent benefits.Methods: Electronic database search in PUBMED, EMBASE, Cochrane library was conducted using search term “tirapazamine”. Randomized or cross-over studies comparing effects of tirapazamine vs other active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…While these results demonstrate the higher cytotoxicity of TPZ under hypoxia, they are in contrast with standard in vitro tests reporting up to ∼500fold cytotoxicity increase under hypoxia in cell suspensions [45]. As clinical data showed that TPZ is only mildly effective in achieving tumor cytotoxicity [14,68,69], the results presented here are more in line with in vivo data. Overall, our system has shown how these two mechanistically-different drugs result in significantly different cytotoxicity under oxygen conditioning.…”
Section: Dox and Tpz Cytotoxicity Under Oxygen Gradientsupporting
confidence: 69%
“…While these results demonstrate the higher cytotoxicity of TPZ under hypoxia, they are in contrast with standard in vitro tests reporting up to ∼500fold cytotoxicity increase under hypoxia in cell suspensions [45]. As clinical data showed that TPZ is only mildly effective in achieving tumor cytotoxicity [14,68,69], the results presented here are more in line with in vivo data. Overall, our system has shown how these two mechanistically-different drugs result in significantly different cytotoxicity under oxygen conditioning.…”
Section: Dox and Tpz Cytotoxicity Under Oxygen Gradientsupporting
confidence: 69%
“…Hypoxia-targeting therapy methods involve direct delivery of oxygen to hypoxic area via nanoparticles, the normalization of tumor vasculature, or the modulation of the HIF signaling pathway [30]. In CC, Tirapazamine was investigated as a potential drug targeting hypoxia; however, clinical and preclinical studies did not demonstrate significant efficacy [102].…”
Section: Other Methodsmentioning
confidence: 99%